Learning with place: exploring nature connection practices on the Earth Kids programme - Emma Brindal (Australian Journal of Environmental Education)
This study investigates nature connection practices in a nonformal place-responsive programme for primary school-aged children in Brisbane, Australia. The practices are explored in terms of their role in making visible the interconnectedness of humans, place and the more-than-human, drawing on posthuman educational theories and practice, in particular common worlds approaches, as well as place pedagogies. The project explores the practices of sit spot, solo wander, journalling, gathering, story-sharing and nature names with a group of children participating in an outdoor homeschool programme. Children’s representations of their experiences in place through story, writing, drawing and the collection of items from nature are analysed to create narrative summaries, which are reflected on and presented with some of the children’s journal entries. The study finds that when integrated together, the nature connection practices: foster embodied and generative place encounters; enable relationships with place and the more-than-human to emerge; cultivate learning with place and (re)story place relations. The paper recommends the use of these nature connection practices in programmes that focus on or integrate outdoor learning in order to generate new understandings about place that recognise the entanglement of humans, place and the more-than-human world.